Sensitivity and specificity for detection of islet cell cytoplasmic antibodies using rat pancreatic sections - Tasaka, Humie; Hasegawa, Yasuko; Takahashi, Kenji (Japanese Journal of Clinical Immunology, 1995)
We determined islet cell cytoplasmic antibodies (ICA) using rat pancreatic sections as a test substrate substitutive for human pancreatic sections by indirect immunoflorescent technique. ICA were measured in sera from 58 patients with insulin-dependent diabetes mellitus (IDDM), 456 with non-insulin-dependent diabetes mellitus (NIDDM), 50 patients with autoimmune diseases, and 110 healthy controls. Seventeen of 58 patients with IDDM showed recent-onset (within 3 months). ICA were also measured in some samples using blood group 0 human pancreatic sections, and the ICA titers were compared with those measured using rat pancreatic sections. The prevalence of ICA was 55.2% (32/58) in patients with IDDM, 1.5% (7/456) in those with NIDDM, 0% (0/50) in those with autoimmune diseases, and 0.9% (1/110) in the healthy controls. Of the 17 recent-onset IDDM ICA were positive in 14 (82.3%). In comparative study of titers for ICA using rat pancreatic sections or human pancreatic sections, rat pancreatic sections yielded ICA titers as high as human pancreatic sections did. These results demonstrate that ICA assay using rat pancreatic sections was diseasespecific, and that antigenicity of the substrate was favorable to ICA. Rat pancreas presents the advantage of greater availability, while providing an identical substrate for ICA. In conclusions, rat pancreatic sections are useful substrate for detecting ICA.